Beyond legislation: reconsidering the locus of power in EU regulatory governance - Eckert, Sandra (The Theory and Practice of Legislation, 2019)
The EU’s character as a regulatory state is widely accepted, yet more research is needed to shed light on the relationship between primary and secondary legislation, as well as other types of rule specification. Applying these concepts to EU rulemaking is insightful since rules adopted through the ordinary legislative procedure (primary legislation) usually only set a broad framework. Yet prior to implementation at the national level, many policies are subject to rule specification through executive decisions (secondary legislation), or through private actors (private regulation). Nevertheless, analysis of the growth of European regulation has mostly focused on primary legislation. By contrast, the question how secondary legislation and private regulation relate to primary legislation has attracted far less attention. I argue in this paper that a focus on primary legislation risks leaving us with a biased account of the power balance in European policymaking. The paper follows a case-oriented strategy with the aim to develop a workable operationalisation of the core concepts. It compares two fields of legislation, namely European product and energy policy. It first retraces the evolution of primary and secondary legislation, but also voluntary agreements as an implementing instrument and the role of private actors’ expertise in these fields, and then assesses the relationship between these regulatory tools based on document analysis and expert interviews. The goal is to work out discrepancies between the formal allocation of competencies and the actual locus of power. The findings show that solely looking at primary legislation leads to several misperceptions, such as overstating the relative importance of certain policy instruments, or the achieved degree of administrative centralisation.
Created from Fastlane, Scopus look-up
Keywords: efficiency; energy policy; environmental policy; Governance; power; primary legislation; private actors; product policy; regulation; regulatory state; secondary legislation; standardisation; voluntary agreements